Expression, Glycoform Characterization, and Antibody-binding of HIV-1 V3 Glycopeptide Domain Fused with Human IgG1-Fc - Yang, Qiang (2010)
The third variable domain (V3) of HIV-1 gp120 envelope glycoprotein is critical for HIV-1 entry and represents an attractive target for vaccine design. There are three conserved N-glycans within or around the V3 loop. The N295 and N332 glycans at the base of V3 are usually characterized as high-mannose type in gp120 and the N301 glycan is a complex type. We report in this paper the expression and characterization of glycosylated, full-size V3 domain derived from HIV-1(Bal) strain as an IgG1-Fc fusion protein, including its binding to two broadly HIV-neutralizing antibodies, 2G12 and 447-52D. It was found that expressing the V3-Fc fusion protein in the HEK293T cells resulted in the production of a glycoform in which all the N-glycans were complex type, in contrast to the glycosylation pattern of V3 in the context of gp120, where the N295 and N332 glycans are high-mannose type. Controlling the glycosylation to restore an epitope of antibody 2G12 was achieved by using an inhibitor of glycan processing enzymes. Mutational studies indicate that the glycan at N301 slightly decreases the binding of V3-Fc to antibody 447-52D, but it can significantly enhance the binding of the V3-Fc to antibody 2G12 when it is changed to a high-mannose type N-glycan. The high-mannose type V3-Fc fusion protein that includes both the 2G12 and 447-52D epitopes represents an interesting immunogen that may be able to raise anti-HIV neutralizing antibodies.